A contribuição da internet na melhoria da qualidade de vida subjetiva do idoso - Pires, Gabriela Silva (2015)
Debates about quality of life emerged in marketing in the 60's, since then it has been a concern of society, including researchers who seek for a long time to understand and to identify the predominant factors of a good life, especially with regard to the elderly, as there is a upward trend in the number of elderly in the world population which makes this public relevant, including in the Brazilian society. When it comes to quality of life in elderly perspective it is important to consider factors that can positively or negatively impact the quality of life of this public, for example, the internet, which is present more and more in daily life of the elderly. It is necessary, thus, to understand how this technology can contribute positively to the quality of life of the elderly. Therefore, this study aimed to analyze the contributions of the use of the Internet to improve the subjective quality of life of the elderly population in the psychological, social and environmental dimensions. From the construction of the theoretical framework, it was observed that most of the concepts of quality of life share common characteristics as general feelings of well-being and satisfaction, social, personal and cultural, encompassing not only on objective areas, but mostly subjective areas. It was found that there is no exact amount of the areas that will make a good life, they can vary in amount and importance depending on the context in question. Thus, quality of life of the elderly can encompass several areas, and you can see specific areas in their daily routines, such as longevity, the meaning of life, sense of usefulness. The areas considered by the elderly in the context of the Internet are even more specific, such as using social networks, making purchases and banking, using websites, among others. From a group of areas discussed in the literature review, three dimensions were defined for this study: psychological dimension, consisting of four areas (emotional well-being, self-esteem, mental health and self-efficacy); social dimension (social interaction and social integration); and environmental dimension (consumption and leisure). The methodological procedures were as follows, in data collection interviews were conducted in depth, qualitative, semi-structured, face to face and individual interviews with 11 elderly residents of Campina Grande, Paraíba. The selection of participants was made by known statements, as well as by snowball. For data analysis we used the content analysis. It was found that most of the elderly participants in the research is retired and uses the internet every day, with the use of time ranging from minutes to hours a day, preferring, most of them, the use of equipment such as personal computer or notebook because they are larger. It was found that in general the Internet contributes positively to the quality of life of the elderly in the three analyzed dimensions, and it may exert a greater or lesser contribution depending on the area of life in question.